The magical world of winnie the pooh Little things mean a lot - Geurs, Karl; Nelson, Steve (Walt Disney Home Entertainment ; Buena Vista Home Entertainment [distributor] ; distributed in the Philippines by Viva Video, 2003)
In The Wishing Bear, Pooh gets all tuckered out when he tries to make his friends' impossible wishes come true. Then, Rabbit gets a true-Pooh gift from the heart in Honey For A Bunny. Everyone's favorite donkey takes up gardening...with hilarious results in Eiyi, Eeyi, Eeyore, and Pooh and the gang mitakenly assume they;re not wanted when a flashy new toy arrives in Monkey See, Monkey Do Better.